PREDICTION OF FINANCIAL DISTRESS BASED ON ACCOUNTING INFORMATION - Dorotheea-Beatrice-Ruxandra CHIOSEA; Camelia-Daniela HAȚEGAN (Annals of the University of Oradea: Economic Science)
When a company goes through a period of economic uncertainty, and its ability to keep operating in the foreseeable is called into question, all stakeholders are affected. In terms of economics a failure means that a company can’t respect the economic principle of going concern, in some situations reaching insolvency or even bankruptcy. The research objective is identifying the key elements regarding the going concern of the companies' activity, and the accounting aspects which are contributing to the analysis of the level of risk faced by a company. According to the accounting rules, the management of the entities bears the responsibility for the preparation of financial statements in accordance with this principle. The hypothesis from which this research starts is that the models of discriminative analysis are the only way to verify the going concern assessment for a long-term period. Following the research, the factors that contribute to the assessment of the principle of going concern were identified, as well as an example of discriminative analysis to assess the risk of bankruptcy that an entity may face, or not in the foreseeable future. The research is based on going concern assessment, but also regarding the usefulness of data collection for business development. At the same time, a series of threats regarding the decision-making processes are pointed out, which may affect the activities of companies. The potential contribution of the study is to develop the literature on a current topic that should be a constant concern of companies, and it can highlight the usefulness of discriminative analysis to predict the financial distress a company may face.